2020
DOI: 10.1111/tbed.13490
|View full text |Cite
|
Sign up to set email alerts
|

Poxviruses diagnosed in cattle from Distrito Federal, Brazil (2015–2018)

Abstract: Vesicular diseases in livestock may be associated with a group of viruses that have significant sanitary, economic and public health relevance. The main diseases of this group are foot and mouth disease (FMD), vesicular stomatitis (VS), bovine herpetic mammillitis (BHM) and the poxvirus infections as bovine vaccinia (BV), bovine papular stomatitis (BPS) and pseudocowpox (PCP). Malignant catarrhal fever (MCF) and bovine viral diarrhoea (BVD) may also

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 25 publications
4
12
0
Order By: Relevance
“…In the current study, the positive cases were observed in all mesoregions of the state, demonstrating that these poxviruses circulate widely in the local bovine herds, but most cases were concentrated in Southern mesoregion. Similar data were detected in a study performed in a federative unit neighbor to Goiás (Alonso et al 2020). Probably, highest notification of cases in the southern mesoregion occurred because this zone is one of the regions with the highest dairy productivity in the state.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…In the current study, the positive cases were observed in all mesoregions of the state, demonstrating that these poxviruses circulate widely in the local bovine herds, but most cases were concentrated in Southern mesoregion. Similar data were detected in a study performed in a federative unit neighbor to Goiás (Alonso et al 2020). Probably, highest notification of cases in the southern mesoregion occurred because this zone is one of the regions with the highest dairy productivity in the state.…”
Section: Discussionsupporting
confidence: 84%
“…Other additional cases of mixed infection by VACV and Orf virus-like parapoxvirus (4%) were identified. A recent study performed in a neighboring Brazilian federative unit showed that the same poxvirus infect cattle of the region with very similar frequencies: 51.92% to VACV, 17.31% to PCPV, 15.38% to BPSV and 9.62% to coinfection (PCPV/BPSV) (Alonso et al 2020). Outbreaks of bovine parapoxviruses have also been diagnosed in other Brazilian regions (Cargnelutti et al 2012, Cargnelutti et al 2014 and in other countries, such as United States (Moeller Jr. et al 2018), Japan (Inoshima et al 2009), Turkey (Şevik 2019), South Korea (Oem et al 2013) and Bangladesh (Lederman et al 2014).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations